A Clinical Pitfall: Optimal Management of Single Dural-based Metastatic Carcinoma of the Breast Mimicking Meningioma. Issue 5 (November 2015) - Li, Chiao-Zhu; Li, Chiao-Ching; Lin, Meng-Chi; Chih-chuan, Hsieh; Chen, Nan-Fu; Chen, Chun-lin; Tang, Chi-Tun
Abstract : Meningioma is the most common benign brain lesion in adults. Conservative treatment is suggested if there is no obvious neurological symptom or mass effect, but cerebral metastases require aggressive therapy. Single dural-based metastatic carcinoma mimicking meningioma is uncommon. Here is a case of clinical dilemma between meningioma and metastatic carcinoma mimicking meningioma. A woman with a history of invasive ductal carcinoma of the breast presented with headache and blurred vision. Brain computed tomography and magnetic resonance imaging (MRI) both gave the impression of meningioma. After surgical resection of the brain lesion, histopathology revealed that it was a metastatic lesion from the breast. This report discussed the optimal management of single dural-based metastatic carcinoma mimicking meningioma.